2016
DOI: 10.1097/md.0000000000005698
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D and “small burden” uterine fibroids

Abstract: The aim of this study was to evaluate the effect of vitamin D supplementation in women with hypovitaminosis D and “small burden” uterine fibroids.This study focused on 208 women diagnosed with uterine fibroids and concomitant hypovitaminosis D, from January to December 2014. One hundred eight women of the initial study population were diagnosed with “small burden” uterine fibroids. Among them, those who underwent a proper vitamin D supplementation constituted the “study group” (n = 53), while women who spontan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 26 publications
5
46
0
2
Order By: Relevance
“…Based on our findings, we suggest that the highest therapeutic benefit of VitD treatment would be from preventing leiomyoma growth and stabilizing its size, thus preventing leiomyomas from reaching a size at which adverse effects would be expected. This approach would be supported by the results of a recent study that showed that patients who were supplemented with VitD showed a lower rate of surgical or medical treatment because of the effect of VitD on leiomyoma progression (47). In addition, VitD treatment could be administered in combination with other treatments when they are temporarily suspended because of their side effects to prevent regrowth of the leiomyoma, thereby offering a great advantage for leiomyoma treatment in current clinical…”
Section: Discussionmentioning
confidence: 98%
“…Based on our findings, we suggest that the highest therapeutic benefit of VitD treatment would be from preventing leiomyoma growth and stabilizing its size, thus preventing leiomyomas from reaching a size at which adverse effects would be expected. This approach would be supported by the results of a recent study that showed that patients who were supplemented with VitD showed a lower rate of surgical or medical treatment because of the effect of VitD on leiomyoma progression (47). In addition, VitD treatment could be administered in combination with other treatments when they are temporarily suspended because of their side effects to prevent regrowth of the leiomyoma, thereby offering a great advantage for leiomyoma treatment in current clinical…”
Section: Discussionmentioning
confidence: 98%
“… 9 10 11 12 13 14 15 16 17 18 Modifiable lifestyle factors that may significantly impact UF incidence include vitamin D deficiency, 7 19 20 21 22 exercise and diet, 23 smoking, 24 obesity, 7 23 25 contraceptive use, 23 and dyslipidemia. 25 26 27 There is some evidence that vitamin D supplementation 28 and statin use 29 have some protective effects. Together, these data suggest that several lifestyle factors may collectively contribute to the development of UF; further studies—including clinical trials of weight loss, exercise, and/or dietary modification for the prevention or treatment of symptomatic UF—are warranted.…”
Section: Burden Of Disease In the United Statesmentioning
confidence: 99%
“…[ 38 ] A study included in our meta-analysis reported that insufficient vitamin D was associated with uterine leiomyoma in white but not black women, which may suggest different latitude and race could influence the risk of female reproductive tumors. [ 6 ] Another influence deserving discussion is the sensitivity and specificity which are expected to be different with diverse detection methods. In the last 4 decades, the detection methods of vitamin D has undergone continuous change from the early competitive binding assays to immunoassay and liquid chromatography and currently mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Taking uterine fibroids as an example, it potentially influences women's health because it results in abnormal uterine bleeding, urinary dysfunction, constipation, pain, infertility, miscarriage, and some pregnancy complications. [ 6 ] Therapies for the female reproductive tumors include surgery, chemotherapy, radiation therapy, and expectant treatments at present. [ 7 ] Patients undergoing these treatments modalities bear higher expenses than expected.…”
Section: Introductionmentioning
confidence: 99%